PENGARUH PENGETAHUAN PERATURAN PAJAK DAN PERSEPSI EFEKTIVITAS SISTEM PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (STUDI KASUS PADA FENOMENA SELEBGRAM KOTA PALEMBANG) - Hadli Universitas IBA; Muhammad Reza Pratama; Ikraam Ikraam (Jurnal Manajemen, 2021)
This study aims to re-examine the effect of knowledge of tax regulations and perceptions of the effectiveness of the taxation system on several celebrities in the city of Palembang. The data used in this study are primary data obtained from questionnaires distributed to respondents. The data that have been collected are 31 questionnaires from 31 questionnaires distributed.The analysis technique used in this research is descriptive statistics, multiple linear regression, classical assumption test, hypothesis testing (t test). Data processing using statistical tools. The results of this study prove that knowledge of tax regulations partially has no effect on taxpayer compliance. However, the perception of the effectiveness of the taxation system has an effect on taxpayer compliance. Meanwhile, simultaneously knowledge of tax regulations, and perceptions of the effectiveness of the taxation system have an effect on taxpayer compliance in several celebrities in the city of Palembang.